2011
DOI: 10.1007/s10689-011-9506-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer other than breast or ovarian in individuals with BRCA1 and BRCA2 mutations

Abstract: The risks of cancers other than breast and ovarian amongst BRCA1 and BRCA2 mutation carriers are based on relatively few family based studies with the risk of specific cancers tested in population based samples of cancers from founder populations. We assessed risks of "other cancers" in 268 BRCA1 families and 222 BRCA2 families using a person years at risk analysis from 1975 to 2005. Cancer confirmations were overall higher than in previous family based studies at 64%. There was no overall increase in risk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
233
5
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(267 citation statements)
references
References 25 publications
16
233
5
7
Order By: Relevance
“…Germline BRCA2 mutations predispose to hereditary breast and ovarian cancer. In some families with BRCA2 mutations, an increased incidence of GC has been encountered [40][41][42][43], with one family fulfilling the HDGC criteria [35].…”
Section: Genetics Of Hdgcmentioning
confidence: 99%
“…Germline BRCA2 mutations predispose to hereditary breast and ovarian cancer. In some families with BRCA2 mutations, an increased incidence of GC has been encountered [40][41][42][43], with one family fulfilling the HDGC criteria [35].…”
Section: Genetics Of Hdgcmentioning
confidence: 99%
“…There remains debate about whether there is an increased risk of PrCa associated with BRCA1 mutations, with some studies reporting no increased risk to those reporting a 1.8-3.75 fold increased risk (Thompson et al, 2002;Leongamornlert et al, 2012;Moran et al, 2012). A number of studies have reported that BRCA2 mutation carriers have more aggressive disease, suggested by their younger age at diagnosis, higher rates of lymph node involvement and distant metastasis at diagnosis, and higher mortality rates compared with non-carriers (Tryggvadóttir et al, 2007;Mitra et al, 2008;Edwards et al, 2010;Gallagher et al, 2010;Thorne et al, 2011;Castro et al, 2013).…”
mentioning
confidence: 99%
“…One of the larger studies to date, completed by the Breast Cancer Linkage Consortium in 1999 found BRCA2 mutation carriers have an increased risk of prostate and pancreatic cancer and an increased risk of buccal cavity, pharyngeal, stomach, gallbladder, andbile ductcancers and melanoma of theskin [5].Theincreased risk of prostate and pancreatic cancer has been replicated by numerous other studies, and the association between BRCA2 mutations and these cancers is accepted in clinical practice [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have debated whether an increased lifetime risk for any cancer beyond breast and ovarian cancer even exists across both sexes and genes [10,12]. Multiple studies have agreed on a significantly increased risk of pancreatic and prostate cancers in BRCA mutation carriers; however, further information regarding the lifetime risks of these cancers is needed [5,7,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation